1996
DOI: 10.1108/09564239610149939
|View full text |Cite
|
Sign up to set email alerts
|

Quality perceptions in the financial services sector

Abstract: Argues that one theme that has emerged consistently in the recent services marketing literature is the importance of frontline employees in service delivery. The internal marketing concept is based on the belief that a firm’s internal market/employees can be motivated to strive for customer‐consciousness, market orientation and sales‐mindedness through the application of accepted external marketing approaches and principles. Considers in this study that these objectives could be achieved by marketing, among ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 46 publications
4
58
0
Order By: Relevance
“…Multiple studies have confirmed the significantly positive relationship between affective commitment and service quality under varying contexts [11,48,49]. Thus, this study proposed the following: H5-1: Affective commitment significantly positively affects service quality.…”
Section: Service Quality and Organizational Commitmentmentioning
confidence: 83%
“…Multiple studies have confirmed the significantly positive relationship between affective commitment and service quality under varying contexts [11,48,49]. Thus, this study proposed the following: H5-1: Affective commitment significantly positively affects service quality.…”
Section: Service Quality and Organizational Commitmentmentioning
confidence: 83%
“…Comparison cases could act as a way forward for building models that may possibly be generalised to a wider population. Whilst authors have tended to discuss employees willingness to 'go the extra mile' in terms of the employment exchange [Rousseau, 1995;Boshoff and Tait, 1996] and internal marketing activities, it is important to recognise that employees may also be driven by social exchange with colleagues. This suggests that employees find themselves in -at least -two exchange relationships.…”
Section: Breaching Contract Expectationsmentioning
confidence: 99%
“…The proposition that organizations depend on employees to deliver quality services to compete and grow has been widely recognized in the services marketing literature (Gronroos, 1990;Boshoff & Tait, 1996;Zeithaml, Berry, & Parasuraman, 1996). Internal marketing (IM) refers to the way in which an organization motivates and educates its employees to behave in a customer-conscious or market-oriented manner through the application of marketing-like processes.…”
Section: Lan Snell and Lesley Whitementioning
confidence: 99%